Old stories, new cases. Viral infectious diseases and children's health - YILDIZ CAMCIOGLU (Elsevier, 2024)
During the 20th century, smallpox has produced between 300-and 500 million victims. In 1796, Edward Jenner conducted one of the first modern immunizations when he inoculated an 8-year-old boy using material from a cowpox lesion. In 1959, WHO (World Health Organization) launched the Smallpox Eradication Programme. By 1980, WHO declared smallpox officially eradicated. Due to genetic and antigenic similarities between the monkeypox and smallpox viruses, the cessation of smallpox vaccination since 1980's contributed to the wanning of cross‐protection against monkeypox (mpox). Outbreaks of human mpox has spread across 110 countries.In 1916 and 1952, two major poliovirus outbreaks took place in the USA. The virus killed or paralyzed over half a million people yearly. Introduction of the inactivated polio vaccine (IPV,1955) and oral polio virus (OPV,1963) led to decline in the number of cases by 99.99 %. The Global Polio Eradication Initiative (GPEI) was launched in 1988 and five of six WHO regions have been certified free of wild polio virus (WPV), except Eastern Mediterranean region. Africa had been declared WPV free, unfortunately cases of paralysis due to wild virus in Malawi and Mozambique were detected having been imported from Pakistan. Outbreaks of circulating Vaccine Derived Polio Virus type 2 (cVDPV2) have expanded in the Eastern Mediterranean and African Region from October 2022 to February 2023. Measles, being one of the most contagious infections, requires high population immunity (>95 %) to impede transmission. In 1963, a measles vaccine became available. Finland was the first country to eradicate measles by using the 2 dose-measles vaccines. The region of the Americas was verified to have eliminated measles in 2000. The COVID-19 pandemic disrupted global vaccination activities. Vaccination coverage has fallen from 90 % to 50 % in western countries. Over 30 000 measles cases were reported from 40 WHO European Region members in 2023.